Exsolution of Nickel Nanoparticles from Mixed‐Valence Metal Oxides: A Quantitative Evaluation by Magnetic Measurements. (28th January 2020) - Tinti, Victor B.; Marani, Debora; Ferlauto, Andre S.; Fonseca, Fabio C.; Esposito, Vincenzo; de Florio, Daniel Z.
Abstract: A fast and accurate experimental method is demonstrated to assess the fraction of exsolved metallic nanoparticles using magnetic measurements. As a benchmark, nanometric metallic nickel exsolved from (La1− x Sr x )(Cr1− y Ni y )O3− δ is used for its high relevance as a solid oxide fuel cell component. The method is based on the difference in the magnetic response of the exsolved metallic nickel (ferromagnetic) and Sr‐doped lanthanum chromite ceramic matrix (paramagnetic). The exsolved nickel results in coherent nanoparticles pinned on the surface of the Sr‐doped lanthanum chromite ceramic matrix, as evidenced by electron microscopy analyses. The results obtained indicate the procedure as a fast and sensitive method to study the exsolution of ferromagnetic nanoparticles. Abstract : A fast and accurate experimental method to assess the fraction of exsolved metallic nanoparticles using magnetic measurements is demonstrated. As a benchmark, nanometric metallic nickel exsolved from (La1− x Sr x )(Cr1− y Ni y )O3− δ is used for its high relevance as a solid oxide fuel cell component. The exsolved nickel results in coherent nanoparticles pinned on the surface of the Sr‐doped lanthanum chromite ceramic matrix.